A27 Pharmacodynamic And Proximal Biomarkers For Modulation Of Huntingtin Levels: Preclincial Studies For Translation To The Clinic. (17th September 2014) - Macdonald, D
Abstract : HTT suppression is a key therapeutic strategy for HD. Reducing the amount of the disease-causing expanded HTT protein in the brain of patients is predicted to slow the progression of the disease. Several approaches are being employed to lower HTT including antisense oligonucleotides and siRNAs, as well as gene therapy approaches using viral delivery of miRNAs, shRNAs, and zinc-finger repressor proteins. To enable the advancement of such therapeutics to the clinic, translatable HTT lowering pharmacodynamic and proximal biomarkers are being explored in preclinical models of HD. Specifically, efforts to identify both molecular and imaging measures that are sensitive to HTT levels will be presented. One or more of these pharmacodynamics markers will be essential measures to demonstrate that the delivery of a HTT lowering therapy does, in fact, lower the amount of HTT in the brains of HD patients.